Switched Control of Cadence During Stationary Cycling Induced by Functional Electrical Stimulation - Bellman, Matthew J.; Cheng, Teng-Hu; Downey, Ryan J.; Hass, Chris J.; Dixon, Warren E. (IEEE transactions on neural systems and rehabilitation engineering, 2016)
Functional electrical stimulation (FES) can be used to activate the dysfunctional lower limb muscles of individuals with neurological disorders to produce cycling as a means of rehabilitation. However, previous literature suggests that poor muscle control and nonphysiological muscle fiber recruitment during FES-cycling causes lower efficiency and power output at the cycle crank than able-bodied cycling, thus motivating the investigation of improved control methods for FES-cycling. In this paper, a stimulation pattern is designed based on the kinematic effectiveness of the rider's hip and knee joints to produce a forward torque about the cycle crank. A robust controller is designed for the uncertain, nonlinear cycle-rider system with autonomous, state-dependent switching. Provided sufficient conditions are satisfied, the switched controller yields ultimately bounded tracking of a desired cadence. Experimental results on four able-bodied subjects demonstrate cadence tracking errors of 0.05 ±1.59 and 5.27 ±2.14 revolutions per minute during volitional and FES-induced cycling, respectively. To establish feasibility of FES-assisted cycling in subjects with Parkinson's disease, experimental results with one subject demonstrate tracking errors of 0.43 ±4.06 and 0.17 ±3.11 revolutions per minute during volitional and FES-induced cycling, respectively.